Discrete propagation model of CDC-based benign worms - LIU Yong1; ZHOU Han-sun3; LIU Tie3; SUN Dong-hong4 (Tongxin xuebao)
According to the idea of constructing CDC（center for disease control）,the characteristics of CDC-based benign worms was analyzed.Furthermore,the process of CDC-based benign worms countering against worms was mod-eled.Finally,the model was simulated.From the simulation,two important factors which affect CDC-based benign worms countering against worms was summarized.